Planning Of Hotel Lighting Installation On Ahmad Yani Street Pontianak - Saputro, Bambang Puji; Abidin, Zainal; Pontia W., F. Trias (Faculty of Engineering, Universitas Tanjungpura, 2025)
The hotel is one of the solutions for a temporary place for a person/group to stay while they do their needs in the area/city so that the calculation of the lighting installation is needed. The hotel consists of 12 floors standing on a land area of 435.2 meters with a hotel length of 25.6 meters, a width of 17 meters, and has a height of 42.2 meters. The hotel consists of 12 floors, namely the 1st floor functions as a lobby and cafe, the mezzanine floor functions as an office, the 2nd floor functions as a meeting room and hotel management, floors 3-12 typically function as hotel rooms. In the Planning of Hotel Lighting Installation on Jalan Ahmad Yani Pontianak must comply with the Indonesian National Standard (SNI) 2011 and the General Regulation of Electrical Installation (PUIL) 2011. At the planning stage several calculations are carried out, namely, calculating the number of lamps, current conductivity, cross-sectional area, power density, and total load. Based on the results of the calculation and analysis, the number of lamps needed is 907 lamps with a total load required of 21.946 kW. The cross-sectional area used is 2 x 1 x 1.5 mm2 using NYY cable and 4 x 1.5 mm2 using NYM cable.